Pure and mixed Scots pine forests showed divergent responses to climate variation and increased intrinsic water use efficiency across a European-wide climate gradient - Shebeshe Assefa; Maurizio Ventura; Felipe Bravo; Giulia Silvia Giberti; Jorge Olivar; Kamil Bielak; Giustino Tonon; Camilla Wellstein (European Journal of Forest Research, 2025)
The present study examined Pinus sylvestris L. growth responses to climatic variations and its relationship with intrinsic water-use efficiency (iWUE) across a water availability gradient and also in pure P. sylvestris and P. sylvestris -Quercus species mixed forests. Study sites were selected in the Mediterranean, temperate, and temperate continental climates in Spain, Italy, and Poland, respectively. A combined tree-ring dendrochronological and stable carbon isotope analysis was used to assess the relationship between tree growth and climate variation. Results showed that P. sylvestris growth is critically affected by summer water availability, regardless of study site and species mixing. Warming temperatures during the early growing season benefit tree growth in Mediterranean and temperate continental climates, while no significant effect was observed in the temperate climatic conditions. At the Mediterranean site, trees in mixed stands showed enhanced growth during wet years when moisture is not limiting. At the temperate continental site, trees in the mixed stand grew at a lower rate than those in pure stands, which suggests that intense interspecific competition for water could overwhelm the benefits of species mixing. Also, we found a divergent growth-iWUE relationship of non-significant and significantly positive and significantly negative correlations at the Polish, Italian, and Spanish sites, respectively. Overall, the negative growth-iWUE relationship at the drier Mediterranean site signifies the risk of tree growth decline, particularly in drier climate conditions. Despite that, elevated iWUE levels would benefit tree radial growth when water is not limited and the admixing tree species have compatible light and water use strategies.